High resolution determination of local residual stress gradients in single- and multilayer thin film systems. (15th January 2016) - Treml, R.; Kozic, D.; Zechner, J.; Maeder, X.; Sartory, B.; Gänser, H.-P.; Schöngrundner, R.; Michler, J.; Brunner, R.; Kiener, D.
Abstract: Residual stresses and stress gradients are of great importance in all thin film systems, as they critically influence the structural stability and functionality, and thus the lifetime, of the concerned devices. In this study, an improved ion beam layer removal method is developed to determine the stress distribution in copper- and tungsten-based thin film systems. Cantilevers were prepared from single, bi- and tri-layer systems with an individual layer thickness of 500 nm using focused ion beam machining. Subsequently, residual stress profiles were determined with a depth resolution of 50 nm, employing the ion beam layer removal method. We observe that the evaluated average film stresses correspond to state-of-the-art X-ray diffraction measurements. However, depending on the layer order, different stress profiles with strong stress gradients evolve, and pronounced changes in residual stress occur across an interface within only few grains. These novel findings have profound implications when addressing the interface adhesion, fracture properties and reliability of novel thin film systems, as well as interface dominated materials in general. Graphical abstract: